IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD CANDRA KASIH - Chindytia; Agung Gede Agung , Anak; Kadek Ayu Sri Utami, Ni; Made Dwi Merta Septiari, Ni; Gusti Ayu Agung Deva Wahyu Wulandari, I (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The quality of a nation’s education is greatly influenced by how educational institutions manage all of their resources. One approach considered capable of addressing this challenge is School-Based Management (SBM), a management model that grants schools greater autonomy to make decisions based on actual needs on the ground. Private schools have their own unique characteristics in the implementation of SBM, as their management involves not only the school itself but also the foundation as the highest authority, meaning that school autonomy operates within the framework of the foundation’s policies. It is this uniqueness that makes the implementation of SBM in private schools an interesting subject for further study. Therefore, this study aims to describe the implementation of SBM at Candra Kasih Elementary School, analyze the roles of the stakeholders involved, and examine its impact on the quality of learning. This study employed a qualitative approach using the case study method, in which data were collected through direct interviews with informants from the school and then analyzed using a descriptive-interpretive approach. The results indicate that the implementation of MBS at Candra Kasih Elementary School is proceeding effectively, as evidenced by systematic program planning, the involvement of various stakeholders in decision-making, the presence of the flagship literacy program “Books Exploring”—which has successfully improved students’ reading skills—and regular evaluations conducted using educational report cards. The principal’s democratic and collaborative leadership also plays a crucial role in supporting the successful implementation of MBS at this school.